Optimization and experiment on key structural parameters of no-tillage planter with straw-smashing and strip-mulching - Shi, Yinyan; Wang, Xiaochan; Hu, Zhichao; Gu, Fengwei; Wu, Feng; Chen, Youqing (International Journal of Agricultural and Biological Engineering, 2021)
Accelerate the quality of smashed-straw laying and enhance the effect of seed-bed arranging for no-tillage planter with straw-smashing and strip-mulching in full stubble covered paddy have become imperative in implementing modern conservation tillage. Considering the perfect operating performance (passability and stability) of the developed no-tillage planter, this study intends to optimize the structure design of smashed-straw diversion device and strip-rotary tillage device. Dynamics equations of smashed straw and kinematics models of rotary blades were established through theoretical analysis, and the principal factors that affecting straw strip-laying quality and seed-bed arranging effect were specified. The influence of out-enlarge angle (η) and slide-push angle (γ) of the diversion device on the coefficient of variation (ζ1) of cover-straw width, and the influence of rotary tillage-blade number (N) and configuration in a single rotary plane on the broken rate (ζ2) of strip soil were completely analyzed. And then, based on the systematic analysis and integrated scheme, operating performance and field verification tests using the optimized no-tillage planter were thoroughly performed. The results of the performance tests indicated that the out-enlarge angle (η) had a highly significant influence on the coefficient of variation (ζ1), and the slide-push angle (γ) had a significant influence on (ζ1). The rotary tillage-blade number (N) had a highly significant influence on the broken rate (ζ2), and the slide-push angle (γ) had a significant influence on (ζ2). The obtained optimal combination of these key structure parameters through comprehensive analysis was η = 45°, γ = 40°, and N = 4. Field verification test results indicated that the optimized no-tillage planter achieved mean values of ζ1 = 10.47% and ζ2 = 90.95%, which satisfied the relevant operation quality and cultivation agricultural requirement of conservation tillage equipment, and provided technical references for developing the similar no-tillage planter of straw crushing and returning. Keywords: no-tillage planter, smashed-straw laying, strip rotary tillage, optimization test DOI: 10.25165/j.ijabe.20211403.5887 Citation: Shi Y Y, Wang X C, Hu Z C, Gu F W, Wu F, Chen Y Q. Optimization and experiment on key structural parameters of no-tillage planter with straw-smashing and strip-mulching. Int J Agric & Biol Eng, 2021; 14(3): 103–111.